Impact of heavy metals on the formation and properties of solvable microbiological products released from activated sludge in biological wastewater treatment. (15th July 2020) - Zheng, Xing; Liu, Tong; Guo, Menghan; Li, Dong; Gou, Na; Cao, Xin; Qiu, Xiaopeng; Li, Xiaoliang; Zhang, Yaozhong; Sheng, Guoping; Pan, Baozhu; Gu, April Z.; et al.
Abstract: This study investigated the acute impact of heavy metals on activated sludge with respect to the amount properties of biopolymers and other solvable microbiological products (SMPs) released from the sludge. Ten heavy metals were selected for the evaluation. Under the experimental conditions, exposing activated sludge to different metals led to an increase in SMPs, with a more significant increase in nitrogenous organics than in carbonaceous ones, where Hg 2+, Ag +, Cu 2+, and Cr 6+ led to the highest increase in SMP species, while Cd 2+, Ni 2+, Mn 2+, Pb 2+, and Co 2+ caused limited increase in the middle and small SMP molecules, and Zn 2+ and Cr 3+ resulted in a decrease in SMP content. To probe the molecular impact of heavy metals and the association between cellular stress and SMP formation, the toxicity of heavy metals was evaluated using a toxicogenomics assay. Based on a correlation analysis between the increase in SMP and the molecular toxicity index-transcriptional effect level index (TELI) of different genes under corresponding stress conditions, eight genes demonstrated a strong correlation with SMP properties and were pre-assumed to have the most significant influence on the increment in SMPs. We further validated the correlation equation established to predict SMP production based on the molecular disturbance of the eight key biomarkers, using arsenic As 3+ and vanadium V 5+ as tests, and by quantifying the amount of SMPs released from the activated sludge under the influence of these metals using a TELI-derived equation. In addition, the heavy metals that generated greater amounts of reactive oxygen species also caused larger increases in SMPs. Graphical abstract: Image 1 Highlights: Test 11 heavy metals on activated sludge soluable microbiological products (SMPs). Thus formed SMPs are of high biopolymer and nitrogen content and hydrophobicity. The severity of the impact can be divided into severe, medium and minor levels. Certain genes were quantitatively identified and confirmed related to SMP formation. The release of SMP is also influenced by the level of reactive oxygen species.